Systolic Time Ratio Measured by Impedance Cardiography Accurately Screens Left Ventricular Diastolic Dysfunction in Patients with Arterial Hypertension - Nazário Leão, R (2017)
BACKGROUND: The use of impedance cardiography (ICG) may play a role in the assessment of cardiac effects of hypertension (HT), especially its hemodynamic features. Hypertensive heart disease involves structural changes and alterations in left ventricular geometry that end up causing systolic and/or diastolic dysfunction. The IMPEDDANS study aims to assess the usefulness of ICG for the screening of left ventricular diastolic dysfunction (LVDD) in patients with HT. METHODS: Patients with HT were assessed by echocardiography and ICG. Receiver-operating characteristic curve and the area under the curve were used to assess the discriminative ability of the parameters obtained by ICG to identify LVDD, as diagnosed by echocardiography. RESULTS: ICG derived pre-ejection period (PEP), left ventricle ejection time (LVET), systolic time ratio (STR) and D wave were associated (p < 0.001) with LVDD diagnosis, with good discriminative ability: PEP (AUC 0.81; 95% CI 0.74-0.89), LVET (AUC 0.82; 95% CI 0.75-0.88), STR (AUC 0.97; 95% CI 0.94-1.00) and presence of D wave (AUC = 0.87; 95% CI 0.82-0.93). STR ≥ 0.30 outperformed the other parameters (sensitivity of 98.0%, specificity of 90.2%, positive predictive value of 95.2%, and negative predictive value of 96.1%). CONCLUSION: The ICG derived value of STR allows the accurate screening of LVDD in patients with HT. It might as well be used for follow up assessment. TRIAL REGISTRATION: The study protocol was retrospectively registered as IMPEDDANS on ClinicalTrials.gov (ID: NCT03209141) on July 6, 2017.